Cultivation of gladiolus Red Majesty fetches more - Nazir, Manoj; Pravin, T. Raj (Indian Horticulture, 2019)
Red Majesty is a newly-developed hybrid from Dutch and properly evolved under Indian conditions under multilocational trials. On an average, it provides 10-12 florets/spike. An ideal and attractive variety for local markets because of shorter rachis length (32 cm). Floret diameter is 9-10 cm. It takes 50-70 days for floret to open having potential of producing 1.5 spikes. A farmer can earn a net profit of ` 245-405/m 2 area of land.